Evaluation of the genes for the adrenergic receptors α2A and α1C and Gilles de la Tourette syndrome - (:unkn) unknown (My University, 2003)
Gilles de la Tourette Syndrome (GTS) has long been known to be familial, and evidence from twin studies indicates that it has a substantial genetic component. Our genome scan of sibling pair families with GTS found evidence suggestive of linkage to several chromosomal locations. On the basis of these findings, we have begun to study additional markers in these regions, with some of the markers located in candidate genes. Two candidate genes stand out in these regions: the adrenergic receptor α1C(1A) (ADRA1C) located on chromosome 8p and the adrenergic receptor α2A (ADRA2A) located on chromosome 10q. The adrenergic system has been suggested to play a role in GTS based on the reduction of symptoms with the adrenergic receptor agonists, clonidine and guanfacine. We examined the inheritance of polymorphisms in the ADRA2A and ADRA1C genes in 113 nuclear families identified through a GTS proband. We found no significant evidence for linkage using the transmission disequilibrium test for these two genes. Based on our families, we conclude that these genes are not major genetic factors contributing to the susceptibility to GTS. © 2003 Wiley-Liss, Inc.
Keywords: Adrenergic receptor α1C (α1a); Adrenergic receptor α2A; Genetics; Gilles de la Tourette syndrome; Linkage